IMMUNOHISTOCHEMICAL STUDY OF WHITE RAT ATRIUM AFTER THE EFFECT OF OPIOID INTOXICATION - Покотило, П.Б. (World of Medicine and Biology, 2014)
Drug use prevalence is stable around the world, according to the 2014 World Drug Report of the United Nations Office on Drugs and Crime (UNODC), with around 182-324 million individuals, or 5 per cent of the world’s population aged 15-64 having used an illicit drug in 2012. It is known that opioids which are used for the treatment of noncancer pain are toxic for human organism. The aim of the present study was thus to investigate the rat atrial cardiac wall on the 7th and 14th day of the experimental opioid intoxication. The male white pubertal rats weighing between 180-200 g were used in these experiments and divided for 3 exercise groups: the 1st group – 30 animals with every day injections of “Nalbufin” (8 mg/kg on 1st week, 15 mg/kg on the 2nd week and 35 mg/kg on 6ᵗ ͪ week ), the 2nd control group 18 animals with every day injections of 1 ml 0,9% NaCl, and the 3rd group – 12 intact animals. In method of immunohistochemistry we used the antibodies to μ–opioid receptors, the antibodies to cleaved Caspase-3 (apoptosis marker) and Phospho-Histone H3 (proliferative processes). This method we performed on the base of Jeff Wrana’s laboratory, Samuel Lunenfeld Research Institute, Mount Sinai Hospital, 600 University Ave Toronto. Results. Our data show that apoptosis start to go in the region of epicardium and perivascular spaces of the atrial myocardium on the 7th day of the experimental opioid intoxication (the 1st exercise group). The great number of cardiomyocytes undergoing apoptosis from the 14th day of the experimental opioid intoxication. We have established some isolated apoptotic cardiomyocytes in the 2nd and 3rd groups of exercise animals. The proliferative processes in the rat atrium start in vascular walls, perivascular spaces of the epicardium on the 7th and 14th day of the experimental opioid intoxication. Proliferation was absent in the region of myocardium and endocardium. Proliferation in atrial vascular walls was insignificant in control and intact groups of exercise animals. The actinum fibers of atrial myocardium become thinner on 7th day of experimental opioid intoxication. Discussion. Nalbufin from opioid group affects apoptosis and proliferative processes on the 7th and 14th day of the experimental opioid intoxication. Conclusions. 1.The apoptosis of atrial myocardium begin to accelerate from 7th day of the experimental opioid intoxication. 2. The proliferative processes in the rat atrium start in vascular walls, perivascular spaces of the epicardium on the 7th day of the experimental opioid intoxication and are continued on the 14th day. 3. The actinum fibers become thinner on the 7th day of experimental opioid intoxication and start to disorder on the 14th day.